Recent progress in synthesis of carbohydrates with sugar nucleotide-dependent glycosyltransferases - Na, Lan (Curr Opin Chem Biol, 2020)
Sugar nucleotide-dependent glycosyltransferases are key enzymes that catalyze the formation of glycosidic bonds in nature. They have been increasingly applied in the synthesis of complex carbohydrates and glycoconjugates with or without in situ generation of sugar nucleotides. Human glycosyltransferases are becoming more accessible and new bacterial glycosyltransferases have been identified and characterized. An increasing number of crystal structures elucidated for glycosyltransferases from mammalian and bacterial sources facilitate structure-based design of mutants as improved catalysts for synthesis. Automated platforms have also been developed for chemoenzymatic synthesis of carbohydrates. Recent progress in applying sugar nucleotide-dependent glycosyltransferases in enzymatic and chemoenzymatic synthesis of mammalian glycans and glycoconjugates, bacterial surface glycans, and glycosylated natural products from bacteria and plants are reviewed.